1981
DOI: 10.1111/j.1476-5381.1981.tb16767.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Forssman‐induced Bronchospasm and Their Inhibition

Abstract: 1 The bronchospasm induced in the guinea-pig by the injection of Forssman antiserum was biphasic in nature in both the sublethal and the lethal reaction. 2 The development of both phases of the bronchospasm in the sublethal reaction was dependent upon the presence of the intact complement system and circulating platelets. In the lethal reaction the phase II bronchospasm did not appear to depend on these factors. 3 The compounds used in this study inhibited phase I bronchospasm of the sublethal reaction in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Removal of circulating platelets (Pinckard et al, 1977;Butler & Smith, 1981;Lellouch-Tubiana et al, 1988) or neutrophils (Wedmore & Williams, 1981;O'Byrne et al, 1984) has been shown to diminish inflammatory reactions. In the present study, neither platelets nor neutrophils contribute to either antigen-induced airway eosinophilia or hyperreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of circulating platelets (Pinckard et al, 1977;Butler & Smith, 1981;Lellouch-Tubiana et al, 1988) or neutrophils (Wedmore & Williams, 1981;O'Byrne et al, 1984) has been shown to diminish inflammatory reactions. In the present study, neither platelets nor neutrophils contribute to either antigen-induced airway eosinophilia or hyperreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Guinea-pig anti-rabbit platelet serum (APS) was a kind gift of Dr K.D. Butler (Ciba-Geigy Pharmaceuticals, Horsham, U.K.), prepared according to the protocol described by Butler & Smith (1982).…”
Section: Preparation Of Anti-platelet Serummentioning
confidence: 99%
“…Histological examination of lungs excised from experimental animals undergoing bronchoconstrictor responses confirms that platelet aggregates are pres ent within the pulmonary vasculature [9,11], How ever, use of histological procedures for routine assess ment of platelet accumulation in experimental ani mals is both laborious and relatively insensitive, since large numbers of animals are needed to define the kinetics of platelet accumulation in any detail. In the present study, a non-invasive technique for continu ous monitoring of platelet accumulation in vivo [12] has been used to investigate the temporal relationship between platelet accumulation and increased airway resistance during responses to PAF-acether or anti gen.…”
Section: Introductionmentioning
confidence: 99%
“…These clin ical observations have an experimental counterpart, since bronchospasm may accompany intravascular aggregation of platelets, or embolization of inert par ticles [3][4][5][6][7], Platelet activation might be considered important in the bronchoconstrictor responses pro duced by collagen [8], Forssman antiserum [9], platelet-activating factor (PAF-acether) [10] or antigen [11], since such responses can be inhibited by pretreat ment with either anti-platelet antiserum or with drugs which inhibit the release reaction of platelets.…”
Section: Introductionmentioning
confidence: 99%